Automatización y pandemia: Amenazas sobre el empleo en América Latina - Cristian Bonavida; Irene Brambilla; Leonardo Gasparini (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2021)
– We study the risk of automation, the unfeasibility of teleworking and the risk of contagion due to physical proximity in the six largest economies in Latin America. We find that workers with low education, informal, and low-wage levels are the most exposed to this type of risk. Automation and health crises may have significant unequalizing effects. In addition, this work provides evidence on interactions between the two risks. Job loss in pandemic situations may be more accelerated in occupations where remote work is less feasible and the risk of automation is higher.
Keywords: J21; J23; J24; O33; 330; covid-19; automation; employment; technology; Latin America